IMPLEMENTASI PENDIDIKAN KARAKTER PADA SISWA KELAS 4 DI SD INPRES LAYANG BERTINGKAT KECAMATAN BONTOALA KOTA MAKASSAR - Nurqadri Nurqadri; Idawati Idawati; Fitri Yanti Muchtar (JURNAL ILMIAH NUSANTARA, 2026)
This research explores the implementation of character education among fourth-grade students at SD Inpres Layang Bertingkat, Bontoala District, Makassar City. The study focuses on the roles of family and school in instilling character values, as well as the significance of synergy between these two environments. The research is motivated by observations of student behaviors such as tardiness, lack of respect for teachers, and academic dishonesty during examinations, which indicate an urgent need for strengthened character development. Using a qualitative approach, this study collected data through interviews and observations involving fourth-grade students, teachers, and school staff. This method allows for an in-depth exploration of information regarding the practices and impacts of character education in real settings. The findings confirm that the family plays a fundamental role in laying the foundation for character education, instilling values of religious devotion, nationalism, independence, mutual cooperation, and integrity through role modeling, effective communication, and positive reinforcement. The school environment complements these efforts by integrating character values into teaching and learning activities as well as extracurricular programs, fostering students who are not only academically proficient but also possess noble character. Synergy between character education at home and at school is crucial in shaping students who are individuals of integrity, responsibility, and readiness to face future challenges.